Vector-borne helminths of dogs and humans in Europe - Otranto Domenico (Parasites & Vectors, 2013)
Abstract Presently, 45% of the total human population of Europe, as well as their domestic and companion animals, are exposed to the risk of vector-borne helminths (VBH) causing diseases. A plethora of intrinsic biological and extrinsic factors affect the relationship among helminths, vectors and animal hosts, in a constantly changing environment. Although canine dirofilarioses by Dirofilaria immitis and Dirofilaria repens are key examples of the success of VBH spreading into non-endemic areas, another example is represented by Thelazia callipaeda eyeworm, an emergent pathogen of dogs, cats and humans in several regions of Europe. The recent finding of Onchocerca lupi causing canine and human infestation in Europe and overseas renders the picture of VBH even more complicated. Similarly, tick-transmitted filarioids of the genus Cercopithifilaria infesting the skin of dogs were recently shown to be widespread in Europe. Although for most of the VBH above there is an increasing accumulation of research data on their distribution at national level, the overall impact of the diseases they cause in dogs and humans is not fully recognised in many aspects. This review investigates the reasons underlying the increasing trend in distribution of VBH in Europe and discusses the diagnostic and control strategies currently available. In addition, this article provides the authors’ opinion on some topics related to VBH that would deserve further scientific investigation.